Lara's gift - O'Brien, Annemarie (New York : Alfred A. Knopf, 2013)
In 1914 Russia, Lara is being groomed by her father to be the next kennel steward for the Count's borzoi dogs unless her mother bears a son, but her visions, although suppressed by her father, seem to suggest she has special bond with the dogs
Includes bibliographical references (p. 183-186)
Keywords: Borzoi -- Fiction; Dogs -- Fiction; Fathers and daughters -- Fiction; Sex role -- Fiction; Visions -- Fiction; Family life -- Russia -- Fiction; Borzoi -- Juvenile fiction; Dogs -- Juvenile fiction; Fathers and daughters -- Juvenile fiction; Sex role -- Juvenile fiction; Visions -- Juvenile fiction; Families -- Russia -- Juvenile fiction; Russia -- History -- 1904-1914 -- Fiction; Russia -- History -- 1904-1914 -- Juvenile fiction